Pengaruh Kualitas Pelayanan dan Harga terhadap Keputusan Pembelian Jasa Ekspedisi CV. Bintang Trans Mandiri Jakarta - Rama Adhitya Nugroho; Jecky Indramarta; Muhammad Rezkullah Effendy (Departement of Mathematics Education, 2023)
This study aims to test empirically the influence of the variables consisting of: The Effect of Service Quality and Price on the Purchase Decision of CV Expedition Services. Star Trans Mandiri Jakarta. The research method used is a quantitative method with a descriptive type of research method. Data analysis techniques in this study used descriptive statistical tests, data instrument tests, classical assumption tests, descriptive analysis, multiple linear analysis, determination tests and hypothesis testing. The sample used in this study was 86 respondents with a random sampling technique on consumers of CV expedition services. Bintang Trans Mandiri Jakarta. Based on the results of hypothesis testing, the results of Service Quality on Purchasing Decisions (Y) with the tcount value of Service Quality are higher than the ttable value or (3.909 > ttable 1.989) with a significance value of 0.000 which means that this value is less than the significance level (0.000 <0. 05). So it can be concluded that partially Service Quality has a significant effect on Purchasing Decisions. This means that Ha1 is accepted and Ho1 is rejected. Based on the results of hypothesis testing, the results obtained are Price on Purchase Decision (Y) with a tcount value of Price higher than the ttable value or (5.660 > ttable 1.989) with a significance value of 0.000 which means that this value is less than the significance level (0.000 <0.05) . So it can be concluded that partially the price has a significant effect on purchasing decisions. This means that Ha1 is accepted and Ho1 is rejected. Based on the Output table 4.29, the results of the Anova test above obtained a Fcount of 135.664 greater than Ftable 3.105 with a significant 0.000 less than 0.05 or (Fcount > Ftable) and (Fsignificant <0.05). So it can be concluded that simultaneously Service Quality and Price together have a significant effect on Purchasing Decisions. Meanwhile, the remaining 23.4% is influenced by other factors outside the independent variables studied.